2021
DOI: 10.3892/mco.2021.2349
|View full text |Cite
|
Sign up to set email alerts
|

Spacers with boluses applied to various sites of oral squamous cell carcinoma: Technical note and retrospective case series

Abstract: The present report describes a case series in which spacers with boluses were used at various sites in the oral cavity to enhance the therapeutic effect of radiation therapy in oral squamous cell carcinoma. In radiotherapy, the surface dose is reduced due to the build-up region of X-rays. In the present study, a bolus was used to complement the build-up region and increase the surface dose effect. A total of 7 patients with oral cancer from a primary care hospital underwent radiation therapy using spacers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In pCT images, the HU range of the EVA material in the paddle blade was between -70 and 140, while the HU range of the tongue was between -20 and 70. Additionally, Baek et al and Yoshizawa et al reported that the customized 3D bolus in the oral cavity resulted in a better dose build-up effect [ 33 , 34 ]. Huang et al found that a 3D printed silicone bite block could reduce the dose to the adjacent normal tissues and improve dosimetric parameters such as dose homogeneity index and conformity index [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pCT images, the HU range of the EVA material in the paddle blade was between -70 and 140, while the HU range of the tongue was between -20 and 70. Additionally, Baek et al and Yoshizawa et al reported that the customized 3D bolus in the oral cavity resulted in a better dose build-up effect [ 33 , 34 ]. Huang et al found that a 3D printed silicone bite block could reduce the dose to the adjacent normal tissues and improve dosimetric parameters such as dose homogeneity index and conformity index [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] ORNs are intractable and significantly reduce the quality of life of survivors of head and neck cancer; therefore, it should be prevented to the greatest extent possible, and the use of spacers during radiation therapy should be considered. [ 12 ] Furthermore, the incidence of radiation-induced secondary cancer, including carcinoma and sarcoma, was reported to be 0.7%, which typically develops >10 to 15 years after radiation therapy. [ 13 ] In the present case, 15 years had passed since radiotherapy, and we suspected the development of a radiation-induced sarcoma because of the rapid growth and atypical histopathological appearance, but it turned out to be NF.…”
Section: Discussionmentioning
confidence: 99%